Hypertension Counseling and Tomato Juice Provision to Lower Blood Pressure in Hypertension Patients in Suka Sari Village, Hamlet 02, Semarang, Kebawetan Subdistrict, Kepahiang Regency - Ria Emalyanda; Feny Triyany; Suci Rohima Janista; Reni Parida; M Syahrul Hamdi; Diyah Tepi Rahmawati; Hengky Tranado; Janista Janista (Universitas Dehasen Bengkulu, 2026)
Hypertension is a common health problem faced by many people and requires simple management that can be carried out independently. The activity